2015
DOI: 10.1513/annalsats.201501-046oc
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-Associated Outcomes in Critically Ill Patients with Malignancies

Abstract: Sepsis is a common cause of critical illness in patients with cancer and remains associated with high mortality. Variables related to underlying malignancy, sepsis severity, and characteristics of infection are associated with a grim prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 31 publications
(40 reference statements)
3
62
1
Order By: Relevance
“…Different infections will impact the host differentially, and even within a single organism, different virulence factors will induce distinct responses. The host response is equally variable, and different genetic, epigenetic, and cellular/subcellular factors lead patients to respond very differently to the identical therapy [124][125][126][127][128][129][130].…”
Section: Which Is the Epidemiology Of Sepsis Susceptibility And Respomentioning
confidence: 99%
“…Different infections will impact the host differentially, and even within a single organism, different virulence factors will induce distinct responses. The host response is equally variable, and different genetic, epigenetic, and cellular/subcellular factors lead patients to respond very differently to the identical therapy [124][125][126][127][128][129][130].…”
Section: Which Is the Epidemiology Of Sepsis Susceptibility And Respomentioning
confidence: 99%
“…While frailty can be readily defined [41, 42], it is difficult to measure in the emergency setting, although attempted by several recent approximated measures [4346]. In particular, patients with IAIs and pre-existing malignant disease have a particular high risk for a poor outcome [47, 48]. …”
Section: Which Patients Are At High Risk Of Failure?mentioning
confidence: 99%
“…Patients with malignancy are at higher risk of developing sepsis than the general population . Particularly, it has been reported that the ICU and in‐hospital mortality rates for cancer patients with sepsis were 42% and 56%, respectively, frequencies that are much higher than immunocompetent patients . While the etiology behind the increased mortality observed in septic cancer patients compared to previously healthy patients is multifactorial (and likely includes exposure to various anticancer drugs), we previously demonstrated that the presence of cancer (in the absence of any other treatment) negatively impacts the mortality following sepsis, and is associated with phenotypic and functional changes in CD4 + T cell responses following sepsis .…”
Section: Introductionmentioning
confidence: 90%
“…that the ICU and in-hospital mortality rates for cancer patients with sepsis were 42% and 56%, respectively, frequencies that are much higher than immunocompetent patients. 6 While the etiology behind the increased mortality observed in septic cancer patients compared to previously healthy patients is multifactorial 7 (and likely includes exposure to various anticancer drugs), we previously demonstrated that the presence of cancer (in the absence of any other treatment) negatively impacts the mortality following sepsis, 8 and is associated with phenotypic and functional changes in CD4 + T cell responses following sepsis. 9 Specifically, cancer mice contained more resting memory and activated CD4 + effector cells, exhibited increased frequencies of PD-1 hi cells that failed to make any cytokines, and a distinct 2B4 hi BTLA hi LAG-3 hi population that secreted more TNF compared to previously healthy (PH) septic controls.…”
Section: Introductionmentioning
confidence: 99%